2010
DOI: 10.1097/sap.0b013e3181ce3929
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinduction in Umbilical Cord- and Palate Periosteum-Derived Mesenchymal Stem Cells

Abstract: Adult abdominoplasty (AA) fat is an ideal source for mesenchymal stem cells (MSCs) because it is discarded after surgery, abundant, and easy to harvest. Children however, do not have the same abundant quantities of fat as adults, nor are they likely to undergo a procedure during which fat is routinely discarded. Hence, finding an alternate source for MSCs in children is a reasonable strategy. Two such sources are the palate periosteum (PP) and the umbilical cord (UC). Advantages for PP as a source of MSCs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 11 publications
0
28
2
Order By: Relevance
“…14 days following incubation in 1:1 adipogenic/osteogenic media, hMSC differentiation was assessed by quantitative protein assays for markers of osteogenesis (alkaline phosphatase, ALP) and adipogenesis (oil red O), gene expression analysis, histological staining for ALP and oil red O, and immunostaining for osteocalcin (OC; osteogenic differentiation) and fatty acid binding protein (FABP; adipogenic differentiation). Our choice of differentiation markers was based on literature demonstrating specificity of each marker to its respective lineage at 14 days following hMSC induction [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…14 days following incubation in 1:1 adipogenic/osteogenic media, hMSC differentiation was assessed by quantitative protein assays for markers of osteogenesis (alkaline phosphatase, ALP) and adipogenesis (oil red O), gene expression analysis, histological staining for ALP and oil red O, and immunostaining for osteocalcin (OC; osteogenic differentiation) and fatty acid binding protein (FABP; adipogenic differentiation). Our choice of differentiation markers was based on literature demonstrating specificity of each marker to its respective lineage at 14 days following hMSC induction [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…These plates are both nonimmunogenic and biodegradable. We have previously demonstrated that these electrospun scaffolds support MSC attachment, migration, proliferation, osteogenic differentiation, and matrix deposition 30,53 ; work by others has demonstrated adequate structural support for treating bone defects in vivo. 54,55 In this study, bone generated using differentiated UC MSCs on PLGA NMFS was better (though not statistically significant) by CT volumetric analysis and histologically similar to the bone generated using cancellous bone from the iliac crest.…”
Section: Figmentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/tec assayed by flow cytometry, as previously described. 30 Passage 0 cells were seeded at a density of 5 · 10 3 cells/cm 2 , grown in Dulbecco's modified Eagle's medium (DMEM) 15% fetal bovine serum (FBS) and sub-passaged at 80% confluence.…”
Section: Figmentioning
confidence: 99%
“…Stem cells have also been isolated from new, more accessible sources, including gingiva [Yang et al, 2013], oral mucosa, palatal connective tissue [Roman et al, 2013], and palatal periosteum [Caballero et al, 2010]. The main goal of the present study was to characterize and compare a novel stem cell population obtained from PAT-and LAT-derived stem cells.…”
Section: Discussionmentioning
confidence: 99%